Fable eaudiobook A novel. - Young, Adrienne (World of the Narrows, 2020)
A REESE WITHERSPOON x HELLO SUNSHINE BOOK CLUB YA PICK Filled with all of the action, emotion, and lyrical writing that brought readers to Sky in the Deep , New York Times bestselling author Adrienne Young returns with Fable , the first audiobook in this new captivating duology. Welcome to a world made dangerous by the sea and by those who wish to profit from it. Where a young girl must find her place and her family while trying to survive in a world built for men. As the daughter of the most powerful trader in the Narrows, the sea is the only home seventeen-year-old Fable has ever known. It's been four years since the night she watched her mother drown during an unforgiving storm. The next day her father abandoned her on a legendary island filled with thieves and little food. To survive she must keep to herself, learn to trust no one and rely on the unique skills her mother taught her. The only thing that keeps her going is the goal of getting off the island, finding her father and demanding her rightful place beside him and his crew. To do so Fable enlists the help of a young trader named West to get her off the island and across the Narrows to her father. But her father's rivalries and the dangers of his trading enterprise have only multiplied since she last saw him and Fable soon finds that West isn't who he seems. Together, they will have to survive more than the treacherous storms that haunt the Narrows if they're going to stay alive. Fable takes you on a spectacular journey filled with romance, intrigue and adventure. A Macmillan Audio production from Wednesday Books "Gripping, immersive, and absolutely masterful, Fable reels you in with the promise of beauty, and holds you tight with Young's signature grit. I couldn't turn the pages quickly enough." -Adalyn Grace, New York Times bestselling author of All The Stars and Teeth "I could taste the salt in the air and feel the waves beneath the Marigold. In a brutal world Fable shines as tenacious yet vulnerable, unafraid to do what she must to survive. This story caught me by the throat and refused to let go!" - Shelby Mahurin, New York Times bestselling author of Serpent & Dove